Evaluating myometrial and cervical invasion in women with endometrial cancer: comparing subjective assessment with objective measurement techniques. (2nd September 2013) - Mascilini, F.; Testa, A. C.; Van Holsbeke, C.; Ameye, L.; Timmerman, D.; Epstein, E.
ABSTRACT Objective To compare the diagnostic accuracy of subjective ultrasound assessment with that of objective measurement techniques in the evaluation of myometrial and cervical invasion in women with endometrial cancer. Methods This was a prospective multicenter study including 144 women with endometrial cancer undergoing transvaginal ultrasound. Myometrial and cervical invasion was evaluated subjectively, as well as objectively measured in different ways: endometrial thickness, tumor/uterine anteroposterior (AP) diameter ratio, minimal tumor‐free margin, minimal tumor‐free margin/uterine AP diameter ratio, tumor volume (three‐dimensional (3D)), tumor/uterine volume (3D) ratio, and distance from outer cervical os to lower margin of tumor (Dist‐OCO). Histological assessment following hysterectomy was the gold standard. Results The sensitivity (72%) and specificity (76%) of tumor/uterine AP diameter (at cut‐off, 0.53) were not significantly different from those of subjective evaluation (sensitivity, 77% (P = 0.44); specificity, 81% (P = 0.32)) for the prediction of deep myometrial invasion; all other objective measurement techniques had either a significantly lower sensitivity or a lower specificity. For all objective measurement techniques, except minimal tumor‐free margin/uterine AP diameter ratio, fixing the sensitivity at the same level as that of subjective evaluation (i.e. 77%) gave a significantly lower specificity. Dist‐OCO was the only parameter that might have potential to predict cervical invasion; it had a non‐significantly higher sensitivity than did subjective evaluation (73% vs 54%, P = 0.06), but a significantly lower specificity (63% vs 93%, P < 0.001). Conclusion Subjective assessment of cervical and myometrial invasion is as good as or better than any objective measurement technique. The tumor/uterine AP diameter ratio and minimal tumor‐free margin/uterine AP diameter ratio seem to be the best objective measurement techniques to predict deep myometrial invasion. It remains to be shown if objective measurements are useful to predict cervical invasion. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.